Separation and structural characterization of the value-added chemicals from mild degradation of lignites: A review. (15th May 2016) - Liu, Fang-Jing; Wei, Xian-Yong; Fan, Maohong; Zong, Zhi-Min
Graphical abstract: Highlights: Review on mild and eco-friendly degradation ways (<400 °C) of lignites is provided. Clean fuels and value-added chemicals can be produced from lignites by mild degradation. Value-added chemicals are characterized by various advanced analytical techniques. Mild, eco-friendly, efficient, and novel lignite conversions need to be developed. Abstract: Lignite utilizations are limited due to the disadvantages of lignites such as high moisture content, high ash yield, and low calorific value. Direct combustion and other conventional utilization processes of lignites emit a huge amount of CO2, leading to catastrophic global warming. Accordingly, mild and eco-friendly utilization technologies should be paid attention to overcome the disadvantages. Separation and structural characterization of organic species in degraded lignites are crucial for producing clean liquid fuels and value-added chemicals. Several molecular and network structural models for lignites have been proposed since 1976 based on the characteristics of the organic species from lignites. Since then, great progress has been achieved in this area, while reviews on the advances have rarely reported. This review focuses on mild (<400 °C) and low-CO2 -emission chemical degradation methods for separating and characterizing value-added chemicals (VACs) from lignites, including low-temperature extraction (LTE), thermal dissolution (TD), extraction in ionic liquids (ILs), and mild oxidation. LTE gives low extract yields for lignites due to strong noncovalent interactions between the soluble organic species (SOSs) and macromolecular network in lignites. Such interactions can be significantly disrupted by TD around 300 °C, leading to dissolving much more SOSs (almost ash-free) which can be used as clean fuels for gas turbines or valuable precursors for chemicals and carbon materials. ILs could be promising green solvents for separating valuable SOSs from lignites. Mild oxidation also proved to be an effective approach for understanding macromolecular structures of lignites and simultaneously producing VACs such as short-chain aliphatic acids and benzenepolycarboxylic acids. Special attention has also been paid to the application of advanced analytical techniques for characterizing the VACs from mild degradation of lignites. Important information on functional groups, carbon and hydrogen forms, molecular mass distributions, and molecular compositions of the VACs can be characterized by using different analytical techniques presented in the review.